2017
DOI: 10.1155/2017/5454263
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Application of Edible Coatings on or before Ultraviolet Treatment on Postharvested Longan Fruits

Abstract: This study compared the effect of application of edible coating on or before ultraviolet treatment on postharvest longan fruits. The treated longan fruits were examined for weight loss, respiration rate, surface color changes, enzymatic activities (PPO, POD, and PAL), and total phenolic contents throughout the 7 storage days at ambient temperature. In addition, coat homogeneity was examined and cell structure of longan flesh at the end of storage was observed. The results showed that when UV was applied before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 43 publications
3
18
0
Order By: Relevance
“…CS coating combined with UV-C irradiation was able to retain a higher level of TP content in longan fruit during 7 days at 28 °C [ 96 ]. Furthermore, Abdipour et al [ 97 ] also demonstrated that the application of both UV lights significantly prevent TP content changes, UV-C irradiated sweet cherry fruit showed a higher retention level of TP content than that observed in UV-B irradiated fruit.…”
Section: Reactive Oxygen Species and Antioxidant Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…CS coating combined with UV-C irradiation was able to retain a higher level of TP content in longan fruit during 7 days at 28 °C [ 96 ]. Furthermore, Abdipour et al [ 97 ] also demonstrated that the application of both UV lights significantly prevent TP content changes, UV-C irradiated sweet cherry fruit showed a higher retention level of TP content than that observed in UV-B irradiated fruit.…”
Section: Reactive Oxygen Species and Antioxidant Systemsmentioning
confidence: 99%
“…Likewise, CS coated fresh cut lemon slices stored at different temperatures showed an increase in GPX activity at high temperature, suggesting that low temperature (0 °C) had an excellent inhibitory effect on the activity of GPX [ 54 ]. Contrarily, in longan fruit, the application of different UV-C and CS-based coating combinations had no significant effect on GPX activity on both pericarp and flesh during seven days of storage [ 96 ]. In guava fruit, composite coating containing CS/Nano-TiO 2 and CS and lemongrass essential oil inhibited GPX activity during storage with lower and higher values in coated fruit at 10 and 15 days of storage, respectively [ 51 , 77 ].…”
Section: Reactive Oxygen Species and Antioxidant Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Delaying of the ripening process and reduction of fruit softening by UVC application have also been reported (Baka et al 1999, Pan et al 2004Pombo et al 2009). Furthermore, some previous studies have shown that the combination of UVC with other preservative methods (edible coatings, heat treatment) have achieved good results in extending the postharvest life of fruits and vegetables and in maintaining their quality (Bal 2019;Pan et al 2004;Lin et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…POD, PPO, PAL activities were tested following the method of Venisse, Malnoy, Faize, Paulin, and Brisset (2002), Chen, Richard, Benhamou, and Timothy (2000), and Lin, Lasekan, Saari, and Khairunniza‐Bejo (2017), respectively. One unit of enzyme activity were defined as the quantity of the enzyme able to produce a 0.01 increase of the absorbance units per min.…”
Section: Methodsmentioning
confidence: 99%